2017
DOI: 10.12962/j23373539.v6i2.25000
|View full text |Cite
|
Sign up to set email alerts
|

Penentuan Kawasan Agropolitan berdasarkan Komoditas Unggulan Tanaman Hortikultura di Kabupaten Malang

Abstract: Malang merupakan salah satu Kabupaten di Jawa Timur memiliki potensi cukup besar di sektor pertanian, kehutanan, dan perikanan dengan memberikan kontribusi terhadap PDRB. Subsektor pertanian, peternakan, dan jasa pertanian serta subsubsektor tanaman hortikultura memberikan kontribusi yang sangat besar terhadap sektor pertanian, kehutanan, dan perikanan. Pada subsubsektor tanaman hortikultura, tanaman buah dan sayur mempunyai nilai produksi komoditas yang tinggi jika dibandingkan dengan tanaman biofarma dan tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Performing a study in Pekalongan Regency, Putri & Kusuma [8] has identified villages with superior commodities and factors influencing the development of these villages as agropolitan centers. They are Legokkalong village in Karanganyar district, Rogoselo village in Doro sub-district, Tlogohendro village in Petungkriono sub-district, and Talun village in Talun sub-district, with a total area of 264.09 km 2 [8,9]. Some superior commodities in the Agropolitan area include avocado, durian, pineapple, potatoes, cabbage, and tomatoes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Performing a study in Pekalongan Regency, Putri & Kusuma [8] has identified villages with superior commodities and factors influencing the development of these villages as agropolitan centers. They are Legokkalong village in Karanganyar district, Rogoselo village in Doro sub-district, Tlogohendro village in Petungkriono sub-district, and Talun village in Talun sub-district, with a total area of 264.09 km 2 [8,9]. Some superior commodities in the Agropolitan area include avocado, durian, pineapple, potatoes, cabbage, and tomatoes.…”
mentioning
confidence: 99%
“…Some superior commodities in the Agropolitan area include avocado, durian, pineapple, potatoes, cabbage, and tomatoes. Further, some factors that influence the development of the villages as agricultural centers development are storage warehouses, agricultural technologies, natural resources, road networks, farmer institutions, government support, and academic involvement [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shift Share Analysis (SSA) Analisis Shift Share dilakukan untuk menentukan komoditas pada subsektor pangan yang mempunyai pertumbuhan progresif yang secara matematis dituliskan sebagai berikut (Sapratama & Erli H, 2013): b) Jika PB bernilai negatif (PB<0), maka komoditas i di Kecamatan j termasuk pada kelompok dengan pertumbuhan yang lambat.…”
unclassified